High‐Activity Fe3C as pH‐Universal Electrocatalyst for Boosting Oxygen Reduction Reaction and Zinc‐Air Battery - Ruan, Qi‐Dong; Feng, Rui; Feng, Jiu‐Ju; Gao, Yi‐Jing; Zhang, Lu; Wang, Ai‐Jun (Small (Weinheim an der Bergstrasse, Germany), 2023)
Transition metal catalysts are regarded as one of promising alternatives to replace traditional Pt‐based catalysts for oxygen reduction reaction (ORR). In this work, an efficient ORR catalyst is synthesized by confining Fe3C nanoparticles into N, S co‐doped porous carbon nanosheets (Fe3C/N,S‐CNS) via high‐temperature pyrolysis, in which 5‐sulfosalicylic acid (SSA) demonstrates as an ideal complexing agent for iron (ΙΙΙ) acetylacetonate while g‐C3N4 behaves as a nitrogen source. The influence of the pyrolysis temperature on the ORR performance is strictly examined in the controlled experiments. The obtained catalyst exhibits excellent ORR performance (E1/2 = 0.86 V; Eonset = 0.98 V) in alkaline electrolyte, coupled by exhibiting the superior catalytic activity and stability (E1/2 = 0.83 V, Eonset = 0.95 V) to Pt/C in acidic media. In parallel, its ORR mechanism is carefully illustrated by the density functional theory (DFT) calculations, especially the role of the incorporated Fe3C played in the catalytic process. The catalyst‐assembled Zn‐air battery also exhibits a much higher power density (163 mW cm–2) and ultralong cyclic stability in the charge–discharge test for 750 h with a gap increase down to 20 mV. This study provides some constructive insights for preparation of advanced ORR catalysts in green energy conversion units correlated systems. The Fe3C/N,S‐CNS is prepared via a convenient one‐pot pyrolysis. The effective coating of Fe3C with a graphite carbon layer alleviates the carbon corrosion and metal loss, enabling the catalyst with outstanding activity and cycling stability for the acidic oxygen reduction reaction (ORR) and Zn‐air battery. According to the DFT calculations, Fe3C acts as the main active site in the catalytic process.